METODE MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN BAHASA ARAB DI MAN 1 SUMBAWA BARAT - Larassati, Minten Ayu (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2023)
Abstract : Â This study aims to reduce learning barriers so that efforts are obtained to improve children’s learning achievement. which is a case study research, data collection is carried out by interview and document methods.Data analysis techniques were performed with miles and huberman models. Based on the results of data analysis, it shows that the obstacles in learning Arabic at MAN 1 West Sumbawa are; (1) students have not mastered the basic language of Arabic (2)Low mastery of Arabic vocabulary. (3) low student interest in learning (4)Students are strongly influenced by the environment outside the school, so students do not focus on learning and are affected by activities that are not needed in order to achieve learning goals. Solutions in improving student learning achievement, namely (1) students who have not mastered the basic knowledge of Arabic, namely with the teacher providing very basic learning materials and providing additional tasks to practice basic Arabic language skills (2) the teacher uses the method of mastering Arabic vocabulary starting from easy to difficult (3) using the memorization method (4) To increase students’ low interest in learning teachers approach students emotionally by giving advice and motivation. It can be concluded that students’ Arabic learning outcomes can be improved by the use of appropriate and good learning methods by teachers in the learning process at school. Â Key Words: Methods, Learning Achievements, Language Arabic.